The Amplitude of Diaphragm Compound Muscle Action Potential Correlates With Diaphragmatic Excursion on Ultrasound and Pulmonary Function After Supraclavicular Brachial Plexus Block - Bao, Xiuxia; Liu, Tao; Feng, Haorong; Zhu, Yeke; Wu, Yingying; Wang, Xianghe; Kang, Xianhui (Frontiers in Medicine, 2022)
Objective: This prospective, single-blind, randomized study assessed the correlations between diaphragm compound muscle action potential (CMAP), hemidiaphragmatic excursion, and pulmonary function after supraclavicular brachial plexus block (SCBPB). The diagnostic efficacy of pulmonary function for hemidiaphragmatic paralysis evidenced by diaphragm CMAP as an assessment of diaphragm strength, was evaluated. Methods: Phrenic nerve conduction studies (PNCS), M-mode ultrasonography of the diaphragm, and pulmonary function tests were performed in 86 patients before and 30 mins after SCBPB. PNCS were used to determine the latency and amplitude of diaphragm CMAP. Ultrasonography of the diaphragm was performed with patients in a supine position using a low frequency probe over the subcostal space at the midclavicular line. Diaphragmatic excursion was measured during quiet breathing and deep breathing. Pulmonary function, including forced vital capacity (FVC), predicted value of FVC, and forced expiratory flow in the first second (FEV1), was measured with spirometry. ROC curve analysis was used to assess the diagnostic efficacy of pulmonary function for hemidiaphragmatic paralysis evidenced by diaphragm CMAP as an assessment of diaphragm strength. Results: There were significant correlations between the reduction in amplitude of diaphragm CMAP and reductions in diaphragmatic excursion during quiet breathing (r=0.70, p<0.001) and deep breathing (r=0.63, p<0.001), when expressed as percentage of baseline values. There were significant correlations between the reduction in amplitude of diaphragm CMAP and reductions in FVC (r=0.67, p<0.001), FVC% (r=0.67, p<0.001), and FEV1 (r=0.62, p<0.001), when expressed as percentage of baseline values. The area under the ROC curve for FVC was 0.86. At a cut off of 0.084, FVC predicted hemidiaphragmatic paralysis (determined by diaphragm CMAP) with a sensitivity and specificity of 79.2% and 100%, respectively. Conclusions: The relative reduction in diaphragm CMAP amplitude after SCBPB correlated with relative reductions in diaphragmatic excursion and pulmonary function. FVC has potential as a useful diagnostic indicator of hemidiaphragmatic paralysis, evidenced by diaphragm CMAP, after SCBPB. These data establish diaphragm CMAP as a direct and objective index of diaphragmatic paralysis after SCBPB.